Capping the Cost of Compliance with the Kyoto Protocol and Recycling Revenues into Land-Use Projects - Bernhard Schlamadinger; Michael Obersteiner; Axel Michaelowa; Michael Grubb; Christian Azar; Yoshiki Yamagata; Donald Goldberg; Peter Read; Miko U. F. Kirschbaum; Philip M. Fearnside; Taishi Sugiyama; Ewald Rametsteiner; et al. (The Scientific World Journal)
There is the concern among some countries that compliance costs with commitments under the Kyoto Protocol may be unacceptably high. There is also the concern that technical difficulties with the inclusion of land use, land-use change, and forestry activities in non-Annex I countries might lead to an effective exclusion of such activities from consideration under the Protocol. This paper is proposing a mechanism that addresses both these concerns. In essence, it is suggested that parties should be able to purchase fixed-price offset certificates if they feel they cannot achieve compliance through other means alone, such as by improved energy efficiency, increased use of renewable energy, or use of the flexible mechanisms in the Kyoto Protocol. These offset certificates would act as a price cap for the cost of compliance for any party to the Protocol. Revenues from purchase of the offset certificates would be directed to forest-based activities in non-Annex I countries such as forest protection that may carry multiple benefits including enhancing net carbon sequestration.